ECM scaffolds mimicking extracellular matrices of endochondral ossification for the regulation of mesenchymal stem cell differentiation. (15th September 2020) - Chen, Yazhou; Lee, Kyubae; Kawazoe, Naoki; Yang, Yingnan; Chen, Guoping
ABSTRACT: Endochondral ossification (ECO) is an important process of bone tissue development. During ECO, extracellular matrices (ECMs) are essential factors to control cell functions and induce bone regeneration. However, the exact role of ECO ECMs on stem cell differentiation remains elusive. In this study, ECM scaffolds were prepared to mimic the ECO-related ECM microenvironments and their effects on stem cell differentiation were compared. Four types of ECM scaffolds mimicking the ECMs of stem cells (SC), chondrogenic (CH), hypertrophic (HY) and osteogenic (OS) stages were prepared by controlling differentiation of human bone marrow-derived mesenchymal stem cells (MSCs) at different stages. Composition of the ECM scaffolds was dependent on the differentiation stage of MSCs. They showed different influence on osteogenic differentiation of MSCs. HY ECM scaffold had the most promotive effect on osteogenic differentiation of MSCs. CH ECM and OS ECM scaffolds showed moderate effect, while SC ECM scaffold had the lowest effect on osteogenic differentiation of MSCs. Their effects on chondrogenic or adipogenic differentiation were not significantly different. The results suggested that the engineered HY ECM scaffold had superior effect for osteogenic differentiation of MSCs. Statement of significance ECM scaffolds mimicking endochondral ossification-related ECM microenvironments are pivotal for elucidation of their roles in regulation of stem cell functions and bone tissue regeneration. This study offers a method to prepare ECM scaffolds that mimic the ECMs from cells at hypertrophic, osteogenic, chondrogenic and stem cell stages. Their composition and impacts on osteogenic differentiation of MSCs were compared. The hypertrophic ECM scaffold had the highest promotive effect on osteogenic differentiation of MSCs. The results advance our understanding about the role of ECO ECMs in regulation of stem cell functions and provide perspective for bone defect repair strategies. Graphical abstract: Image, graphical abstract